APPLICATION OF CRIMINAL SANCTIONS FOR VIOLATIONS OF SELLING IN PROHIBITED PLACES - Novi Juli Rosani Zulkarnain; Hairul Amren Samosir (CV. RADJA PUBLIKA, 2024)
Implementation of criminal sanctions for violations of selling in prohibited places. The formulation of the problem in this study is the factors causing violations of selling in prohibited places, obstacles received in the process of resolving cases of Violations of Selling in Prohibited Places and what is done in implementing sanctions for violations of selling in prohibited places. The purpose of the study is to determine the factors causing violations of selling in prohibited places, to determine the obstacles received in the process of resolving cases of Violations of Selling in Prohibited Places and to determine what efforts are made in implementing sanctions for violations of selling in prohibited places. The results of this study indicate that the factors causing violations of selling in prohibited places are the limited availability of adequate jobs accompanied by an increase in the number of unemployed, economic difficulties, the existence of business opportunities with little capital and quite in demand by many people who are economically affected and the existence of a very rapid flow of urbanization. The obstacles received in the process of resolving cases of Violations of Selling in Prohibited Places consist of internal factors and external factors. Efforts made in implementing sanctions against violations of selling in prohibited places are to increase government attention to street vendors through the provision of adequate and suitable locations, increasing prevention activities through officer patrols and increasing self-security in each environment, both residential and vital places. The government should be able to provide a solution by providing a proper and appropriate place to sell for street vendors so that their existence does not disrupt public order.